2010
DOI: 10.9755/ejfa.v22i4.4875
|View full text |Cite
|
Sign up to set email alerts
|

Nodule formation, distribution and symbiotic efficacy of Vigna unguiculata L. under different soil salinity regimes

Abstract: Rhizobium-legume symbiosis is one of the most well-established symbiotic nitrogen fixing system for agronomic studies. The current study aimed to test the hypothesis that screening for salt-tolerant rhizobial strains or salt-tolerant cultivar does not necessarily promise a salttolerant symbiotic system, as the symbiotic system is more sensitive to salt stress than the bacterium and/or the plant. In fact, the current study reveals that there is a decrease in salt tolerance of the symbiotic system by 1 dS/m , an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Mahmood and Iqbal (1994) observed that nodules in sesbania and lablab were globose with or without reticulate surface, elongated in pigeonpea and distributed both on primary and secondary roots in all. Nodules formed on primary roots are considered to be more efficient than those on the secondary roots and in cowpea, and a gradual shift was observed in the spatial distribution of nodules from primary roots to secondary roots under increased salt-levels (Predeepa and Ravindran, 2010).…”
Section: Results and Discussion Nodule Characteristicsmentioning
confidence: 99%
“…Mahmood and Iqbal (1994) observed that nodules in sesbania and lablab were globose with or without reticulate surface, elongated in pigeonpea and distributed both on primary and secondary roots in all. Nodules formed on primary roots are considered to be more efficient than those on the secondary roots and in cowpea, and a gradual shift was observed in the spatial distribution of nodules from primary roots to secondary roots under increased salt-levels (Predeepa and Ravindran, 2010).…”
Section: Results and Discussion Nodule Characteristicsmentioning
confidence: 99%
“…Nitrogen-fixing root nodules are organs that need to assimilate large amounts of energy source in the form of photosynthate products either for the formation of nodule primordium (Complainville et al, 2003) and to provide energy for the N fixation performed by the Rhizobium and assimilation of the produced ammonium and starch biosynthesis (Dilworth et al, 2008). Rhizobium-legume has the ability to develop a partnership for forming nodules as a repository for fixing nitrogen that can be used by the legume and energy resources for the bacterium (Predeepa and Ravindran, 2010).…”
Section: The Influence Of Bnf To Root Length Number and Weight Of Nomentioning
confidence: 99%
“…However, the species vary in tolerance to environmental stresses (Sridhar et al, 2005;Wei et al, 2008;Biswas et al, 2008). The rhizobial strains from various grain legumes may tolerate 100-300 mM concentrations of NaCl (Predeepa & Ravindran, 2010). Leguminous plants growing in saline environments require both the rhizobia and the host to be tolerant to salt.…”
Section: Rhizobia-legume Symbiosis and Stressmentioning
confidence: 99%
“…The response of legumes to environmental stresses such as salinity and drought varies and depends on soil type, salt toxicity and climatic factors (Cordovilla et al, 1995;Serraj et al, 2001;Predeepa & Ravindran, 2010;Jabborova et al, 2013a). Numerous studies have shown that soil salinity inhibits legume growth and development and decreases nodulation and N 2 fixation (reviewed by Zahran, 1999;Mensah & Ihenyen, 2009;Egamberdieva et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%